(untitled) (Comprehensive Journal of Science, 2025)
The permanent magnet fault current limiter (PMFCL) offers several significant advantages, including compactness, high reliability, zero reset time, safe operation, and inherent fail-safe characteristics, making it a highly viable solution for moderating fault currents in power system networks. This paper presents the design of a low-voltage (480 V) PMFCL. The proposed industrial device can be used with the existing oil production 480V motor control center (MCC) switchgear facilities across Libya and considerably for other proposed future renewable energy sources. Three-dimensional finite element method (3D FEM) simulations confirm that the advanced industrial low voltage PMFCL device operates effectively and reliably under both fault conditions and normal operation within the power distribution network.